(untitled) (Indian Journal of Child Health, 2025)
Lingual thyroid gland is a rare entity which occurs due to the failure of the thyroid gland to descend into its usual pretracheal position during embryogenesis. The reported incidence of lingual thyroid is more common in females. When located at the base of the tongue, ectopic thyroid gland is often asymptomatic but may cause local symptoms such as difficulty in swallowing, hoarseness and a foreign body sensation in the throat, hemorrhage and often presents with hypothyroidism. The diagnosis of lingual thyroid is usually made clinically along with imaging studies and radionuclide scanning is used to confirm diagnosis. A case of lingual thyroid with right internal jugular vein phlebectasia in a 4-year-old male is presented for its rarity and for differential diagnosis of midline base of the tongue lesions.